If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -21 + -1x = 44 + -6x Solving -21 + -1x = 44 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -21 + -1x + 6x = 44 + -6x + 6x Combine like terms: -1x + 6x = 5x -21 + 5x = 44 + -6x + 6x Combine like terms: -6x + 6x = 0 -21 + 5x = 44 + 0 -21 + 5x = 44 Add '21' to each side of the equation. -21 + 21 + 5x = 44 + 21 Combine like terms: -21 + 21 = 0 0 + 5x = 44 + 21 5x = 44 + 21 Combine like terms: 44 + 21 = 65 5x = 65 Divide each side by '5'. x = 13 Simplifying x = 13
| 13x-7+7x=180 | | -3x-10=8-6x | | X-7y-15=0 | | 12a+10a-4+6a+8+6a+8=102 | | 6w^2+34w+41= | | 4(4x-3)+4x=-132 | | x-31=60-6x | | 17x^2+-46x+48=7x^2 | | 34a+12=102 | | 5(x+7)=5x-35 | | 7-0.5y=-1-.05y | | 2d+34+3d=84 | | 1=-4x+9y | | 17x+7=19x-5 | | 20-40x=5 | | x-31=60-7x | | -x+35=2x+14 | | 10x-6=8x+10 | | 2x*2x=72 | | a^3-3a^2=40a | | W^2+2w+8=0 | | -4p+9=-8.48 | | 4(4(6)-3)+4(6)=-132 | | 6y=4x+4 | | -53+25= | | 8r^2+4r+9=0 | | -3x-2(4x+4)=69 | | s-7=-2 | | 2t-5=1+t | | 12x-9=3z | | 4(4(6)+3)+4(6)=-132 | | 2x+3(2/3x+4)=-6 |